RSIS High-Level Trade Policy Meeting – Looking into the Trade Abyss - Rogerson, Evan (2019)
With the outbreak of large-scale trade wars around the world, and the pressures nationalist governments have applied on the World Trade Organisation (WTO), there is an urgent need for an in-depth evaluation of the perils and possibilities for trade policy.